Pocket-size commemorative edition on the occasion of the 30th anniversary of the adoption of the African Charter on Human and Peoples' Rights 1981 - 2011 (Pretoria University Law Press (PULP), 2011)
Pocket-size commemorative edition on the occasion of the 30th anniversary of the adoption of the African Charter on Human and Peoples' Rights 1981 - 2011 2011 ISBN: 978-0-9869857-5-1 Pages: 87 Print version: Available Electronic version: Free PDF available